(untitled) (International Journal of Engineering and Computer Science, 2013)
Security is one of the key aspects for public safety. Packages and luggage should be examined for weapons, narcotics and explosive devices by security system to ensure safety at places like airports, parliament house, banks, etc. One such system is X-ray Baggage Inspection System (XBIS). An X-ray generator supplies required radiation during screening and emitted Xrays penetrate through object under examination while passing through unit. Screening of luggage is don slice by slice and hence obtained picture information is then stored, processed to an extraordinary clear, informative complete image and finally reproduced on monitor screen. X-ray TV image generated in accordance with scanning principle where item of luggage is routed past linear detector line by means of conveyor belt. This detector line consists of X-ray sensor amplifiers mounted on PCBs. This project deals with design of X-ray sensor amplifiers. At detector side of XBIS set of X-ray sensor amplifiers on PCBs are arranged in horizontal and vertical lines on another side of X-ray generator. Two sets of 16 PCBs are arranged one above other in two layers for lower and higher energy perception. Diodes in a line are scanned by incrementing the address also the object is screened line-by-line as it moves on conveyor belt. Hence obtained picture information on screen presents information of objects and its inner parts taking advantage of penetration of X-rays through the objects.